Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To answer the question, we need to evaluate the two given summations and then find the difference between them.
### Step 1: Evaluate [tex]\(\sum_{n=0}^4(1+3n)\)[/tex]
We need to find the sum of the expression [tex]\(1 + 3n\)[/tex] as [tex]\(n\)[/tex] goes from 0 to 4:
- For [tex]\(n = 0\)[/tex]: [tex]\(1 + 3(0) = 1\)[/tex]
- For [tex]\(n = 1\)[/tex]: [tex]\(1 + 3(1) = 4\)[/tex]
- For [tex]\(n = 2\)[/tex]: [tex]\(1 + 3(2) = 7\)[/tex]
- For [tex]\(n = 3\)[/tex]: [tex]\(1 + 3(3) = 10\)[/tex]
- For [tex]\(n = 4\)[/tex]: [tex]\(1 + 3(4) = 13\)[/tex]
Now, add these values together:
[tex]\[ 1 + 4 + 7 + 10 + 13 = 35 \][/tex]
So, [tex]\(\sum_{n=0}^4(1+3n) = 35\)[/tex].
### Step 2: Evaluate [tex]\(\sum_{i=2}^6(3i-5)\)[/tex]
We need to find the sum of the expression [tex]\(3i - 5\)[/tex] as [tex]\(i\)[/tex] goes from 2 to 6:
- For [tex]\(i = 2\)[/tex]: [tex]\(3(2) - 5 = 6 - 5 = 1\)[/tex]
- For [tex]\(i = 3\)[/tex]: [tex]\(3(3) - 5 = 9 - 5 = 4\)[/tex]
- For [tex]\(i = 4\)[/tex]: [tex]\(3(4) - 5 = 12 - 5 = 7\)[/tex]
- For [tex]\(i = 5\)[/tex]: [tex]\(3(5) - 5 = 15 - 5 = 10\)[/tex]
- For [tex]\(i = 6\)[/tex]: [tex]\(3(6) - 5 = 18 - 5 = 13\)[/tex]
Now, add these values together:
[tex]\[ 1 + 4 + 7 + 10 + 13 = 35 \][/tex]
So, [tex]\(\sum_{i=2}^6(3i-5) = 35\)[/tex].
### Step 3: Find the difference between the two sums
We have:
[tex]\[ \sum_{n=0}^4(1+3n) = 35 \][/tex]
[tex]\[ \sum_{i=2}^6(3i-5) = 35 \][/tex]
The difference between the two sums is:
[tex]\[ 35 - 35 = 0 \][/tex]
Therefore, the difference between [tex]\(\sum_{n=0}^4(1+3n)\)[/tex] and [tex]\(\sum_{i=2}^6(3i-5)\)[/tex] is [tex]\(0\)[/tex].
Among the given options, the correct answer is:
[tex]\[ 0 \][/tex]
### Step 1: Evaluate [tex]\(\sum_{n=0}^4(1+3n)\)[/tex]
We need to find the sum of the expression [tex]\(1 + 3n\)[/tex] as [tex]\(n\)[/tex] goes from 0 to 4:
- For [tex]\(n = 0\)[/tex]: [tex]\(1 + 3(0) = 1\)[/tex]
- For [tex]\(n = 1\)[/tex]: [tex]\(1 + 3(1) = 4\)[/tex]
- For [tex]\(n = 2\)[/tex]: [tex]\(1 + 3(2) = 7\)[/tex]
- For [tex]\(n = 3\)[/tex]: [tex]\(1 + 3(3) = 10\)[/tex]
- For [tex]\(n = 4\)[/tex]: [tex]\(1 + 3(4) = 13\)[/tex]
Now, add these values together:
[tex]\[ 1 + 4 + 7 + 10 + 13 = 35 \][/tex]
So, [tex]\(\sum_{n=0}^4(1+3n) = 35\)[/tex].
### Step 2: Evaluate [tex]\(\sum_{i=2}^6(3i-5)\)[/tex]
We need to find the sum of the expression [tex]\(3i - 5\)[/tex] as [tex]\(i\)[/tex] goes from 2 to 6:
- For [tex]\(i = 2\)[/tex]: [tex]\(3(2) - 5 = 6 - 5 = 1\)[/tex]
- For [tex]\(i = 3\)[/tex]: [tex]\(3(3) - 5 = 9 - 5 = 4\)[/tex]
- For [tex]\(i = 4\)[/tex]: [tex]\(3(4) - 5 = 12 - 5 = 7\)[/tex]
- For [tex]\(i = 5\)[/tex]: [tex]\(3(5) - 5 = 15 - 5 = 10\)[/tex]
- For [tex]\(i = 6\)[/tex]: [tex]\(3(6) - 5 = 18 - 5 = 13\)[/tex]
Now, add these values together:
[tex]\[ 1 + 4 + 7 + 10 + 13 = 35 \][/tex]
So, [tex]\(\sum_{i=2}^6(3i-5) = 35\)[/tex].
### Step 3: Find the difference between the two sums
We have:
[tex]\[ \sum_{n=0}^4(1+3n) = 35 \][/tex]
[tex]\[ \sum_{i=2}^6(3i-5) = 35 \][/tex]
The difference between the two sums is:
[tex]\[ 35 - 35 = 0 \][/tex]
Therefore, the difference between [tex]\(\sum_{n=0}^4(1+3n)\)[/tex] and [tex]\(\sum_{i=2}^6(3i-5)\)[/tex] is [tex]\(0\)[/tex].
Among the given options, the correct answer is:
[tex]\[ 0 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.